2011
DOI: 10.4028/www.scientific.net/amr.324.360
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mechanical Behavior of Chips Reinforced Concrete

Abstract: Mechanical behavior of steel fiber reinforced concrete has been studied by the direct tensile test. This fiber concrete is obtained by adding machining chips to the bare concrete. Six fiber contents were adopted (W=0.4%, 0.6%, 0.8%, 1%, 1.2% and 1.5%) for two sand over gravel ratio (S/G = 0.8 and S/G = 1). The results obtained showed that the fibers have substantially improved the stiffness and the strength of concrete and conferred a significant ductility to the material for the fiber volume fractions 0.4%, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For W less than 1%, the sand over gravel ratio S/G =1 shows better characteristics. This result is in good agreement with the one given in [3]. that of the classic fiber one represents 56% for tension, 100% for compression, 74% for bending and 30% for splitting.…”
Section: Key Engineering Materials Vols 592-593supporting
confidence: 93%
See 1 more Smart Citation
“…For W less than 1%, the sand over gravel ratio S/G =1 shows better characteristics. This result is in good agreement with the one given in [3]. that of the classic fiber one represents 56% for tension, 100% for compression, 74% for bending and 30% for splitting.…”
Section: Key Engineering Materials Vols 592-593supporting
confidence: 93%
“…Characterization by Simple Compression Test. The stress-strain curves, describing the compression behavior of chips reinforced concrete are identical to those given in [3]. The addition of chips in a small percentage (W = 0.4%) provides a slight increase in resistance (18%) and rigidity.…”
Section: Resultsmentioning
confidence: 61%
“…Experimental studies have been conducted to replace the reinforcements of reinforced concrete with bers capable of providing good tensile, exural, and shear strength to concrete [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Initially, researchers attempted to increase the mechanical characteristics of concrete such as compressive strength and exural strength by adding bers, but the result obtained was limited [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, the calculation of the equilibrium of the forces in a cracked section makes it possible to know the resistance capacity in flexion. An experimental study of the mechanical behavior of reinforced concrete with chips was made by Djebali et al (2011) using direct tensile tests. The authors concluded that the fibers substantially improved the stiffness and the strength of the concrete.…”
Section: Introductionmentioning
confidence: 99%